Treatment of Collapsible Soils with Granulated Blast Furnace Slag and Calcined Eggshell Waste - Adjabi, Souhila; Nouaouria, Mohamed Salah; Djebabla, Wafa (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In order to meet environmental and socio-economic challenges, the recycling of waste tobe used in the treatment of geotechnical problems is one of the main ways of preserving the environment with a lower economic value. The objective of this experimental work is to improve the characteristics and to study the mechanical behaviour of collapsible soil treated with a new hydraulic stabilizer composed of Crushed Granulated Blast Furnace Slag (CGBS) active by Eggshell Waste (CES).
Keywords: recycling of waste; shear strength; cohesion; internal friction angle; blast furnace slag; calcined eggshell; collapsible soil; compaction energy; recykling odpadów; spójność; kąt tarcia wewnętrznego; żużel wielkopiecowy